2014
DOI: 10.2174/1570159x1201140117162802
|View full text |Cite
|
Sign up to set email alerts
|

Pregabalin in Neuropathic Pain: Evidences and Possible Mechanisms

Abstract: Pregabalin is an antagonist of voltage gated Ca2+ channels and specifically binds to alpha-2-delta subunit to produce antiepileptic and analgesic actions. It successfully alleviates the symptoms of various types of neuropathic pain and presents itself as a first line therapeutic agent with remarkable safety and efficacy. Preclinical studies in various animal models of neuropathic pain have shown its effectiveness in treating the symptoms like allodynia and hyperalgesia. Clinical studies in different age groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
126
1
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(134 citation statements)
references
References 125 publications
4
126
1
3
Order By: Relevance
“…Based on these findings, it has been suggested that co-administration of the mentioned AEDs with losartan may affect motor coordination in mice through modulation of GABAergic and/or dopaminergic systems [7,16,17]. Regarding pregabalin, motor coordination impairment and ataxia belong to the most common side-effects in patients treated with this drug [22]. Pregabalin is a potent ligand of α 2 δ type 1 and 2 subunits of voltage-gated calcium channels in the central nervous system, and through binding to the α 2 δ site it decreases calcium inward currents with a consequential modulation in excitatory neurotransmitter release [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these findings, it has been suggested that co-administration of the mentioned AEDs with losartan may affect motor coordination in mice through modulation of GABAergic and/or dopaminergic systems [7,16,17]. Regarding pregabalin, motor coordination impairment and ataxia belong to the most common side-effects in patients treated with this drug [22]. Pregabalin is a potent ligand of α 2 δ type 1 and 2 subunits of voltage-gated calcium channels in the central nervous system, and through binding to the α 2 δ site it decreases calcium inward currents with a consequential modulation in excitatory neurotransmitter release [23].…”
Section: Discussionmentioning
confidence: 99%
“…Pregabalin is a potent ligand of α 2 δ type 1 and 2 subunits of voltage-gated calcium channels in the central nervous system, and through binding to the α 2 δ site it decreases calcium inward currents with a consequential modulation in excitatory neurotransmitter release [23]. The highest level of expression of these channels has been found in the cerebellum and in the hippocampus [22]. It is suggested that their dysfunction/decreased activity may affect the vestibulocerebellar/brainstem structures and higher cortical functions leading to dizziness, blurred vision, ataxia and cognitive impairment [22].…”
Section: Discussionmentioning
confidence: 99%
“…Neuropathic pain is one component of postoperative pain [12]. There are different methods to restrain postoperative pain but all these methods may be not enough for many patients [13]. Many studies showed that pregabalin (when given preoperatively) plays a remarkable role to restrain postoperative pain [14].…”
Section: Discussionmentioning
confidence: 99%
“…Both xylopic acid and pregabalin are calcium channel blockers with the ability to stabilise injured nerve membrane. 24,25 This mechanism may underline the analgesic effect of the co-administered agents in the thermal pain test because additivity is at best observed when two agents activate the same pathway. 15 Xylopic acid produces analgesic effect in neuropathic pain by acting on NMDA and adrenergic nociceptive pathways.…”
Section: Discussionmentioning
confidence: 99%
“…12 Any of these nociceptive pathways might have been modulated by xylopic acid in addition to the inhibition of Ca 2+ channel-mediated neurotransmitter release, activation of excitatory amino acid transporters, modulation of potassium channels and inhibition of pathways involving inflammatory mediators by pregabalin to produce the observed synergism in the cold allodynia test. 24 Although xylopic acid and pregabalin co-administration produced analgesic synergism and additivity, the combination may not be without toxic effects, especially on prolong usage. Paclitaxel slightly reduced the red blood cells and platelets count and these effects were reversed by the co-administered agents.…”
Section: Discussionmentioning
confidence: 99%